2017
DOI: 10.3389/fnagi.2017.00172
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Propionate Exacerbates the Deficits of Nigrostriatal Dopaminergic System and Downregulates Nrf2 Expression in Reserpine-Treated Aged Male Rats

Abstract: There is a controversy over the effects of testosterone supplements on dopaminergic function. Both neuroprotective and toxic effects of testosterone supplements are reported. The status of oxidative stress seems to explain the neuroprotective or toxic properties of testosterone. To determine the efficacy of testosterone supplements in different status of oxidative stress, the present studies analyzed the dopamine (DA)-related behaviors and neurochemical indices, as well as markers of nigrostriatal dopaminergic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 64 publications
1
20
0
2
Order By: Relevance
“…Oxidative stress is one of the most significant factors that causes dopaminergic system disturbances. The factor, aging, leads to dopamine auto-oxidation [9] and testosterone may enhance oxidative stress-related neurotoxicity in dopaminergic neurons and then lead to apoptosis [15]. Furthermore, it has been demonstrated that short-term and long-term stress may cause the reduction of blood testosterone levels and modified oxidative redox [13].…”
Section: Testosterone and Oxidative Stressmentioning
confidence: 99%
See 3 more Smart Citations
“…Oxidative stress is one of the most significant factors that causes dopaminergic system disturbances. The factor, aging, leads to dopamine auto-oxidation [9] and testosterone may enhance oxidative stress-related neurotoxicity in dopaminergic neurons and then lead to apoptosis [15]. Furthermore, it has been demonstrated that short-term and long-term stress may cause the reduction of blood testosterone levels and modified oxidative redox [13].…”
Section: Testosterone and Oxidative Stressmentioning
confidence: 99%
“…Moreover, it was reported that there was a positive correlation between the quantity of spicy food (eating behavior) and endogenous salivary testosterone [8]. Testosterone may regulate the behaviors of organisms by affecting central dopaminergic system [9]. Testosterone affects brain functions including motor, cognitive, and motivational behaviors and dopamine release in midbrain circuits [10].…”
Section: Testosterone and Dopaminergic Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, long-term use of reserpine increases cholinergic tonus; and by suppressing adrenergic activity, it leads to gastric mucosal lesion with an increase in gastric acid production and motility (6). Some studies indicate that reserpine has strong oxidant activity in plasma and tissues (7)(8)(9). In spite of all these effects, reserpine is still used in China as it is more effective and cheaper along with other hypotensive drugs such as compound hypotensive tablets (CHTs) and compound reserpine tablets (5).…”
Section: Introductionmentioning
confidence: 99%